Evaluation of the Integrity of Horse Hoof Dermal and Epidermal Tissues Collected by Dorsal Transmural Access - Gravena, Kamila [UNESP]; de Lima Sampaio, Rita de Cassia [UNESP]; Martins Dias, Deborah Penteado [UNESP]; Canola, Paulo Alescio [UNESP]; Peiro, Juliana Regina [UNESP]; de Lacerda-Neto, Jose Correa [UNESP] (Elsevier B.V., 2012)
The purpose of this study was to evaluate the integrity of dermal and epidermal tissues collected by dorsal transmural access. Eight healthy adult horses were subjected to two biopsies of the right hoof, with a 24-hour interval. To ensure hoof integrity, a radiographic evaluation with dorsopalmar and lateromedial positions was performed. The animals were sedated, and the pedal tissue was collected from two sites that were 2 cm distal to the coronary band. For each biopsy, the hoof wall was perforated using an aluminum oxide drill bit, 4.8 mm in diameter that was connected to a drilling machine, yielding a hole of approximately 9.0 mm. The perforation procedure was performed slowly in the stratum medium until 1 mm of it remained, which was determined by evaluating the movement in response to pressure applied with a Halstead forceps. Laminar deep incisions were performed with a number 11 scalpel blade until the distal phalanx was reached. The laminar tissue was then removed using a Frahm scaler. A cuboid laminar sample measuring approximately 5 mm at the base and 7 mm in height was obtained. The samples were suitable for analysis by histology and transmission electron microscopy showing that the ends of the secondary epidermal laminae were round, the basement membrane was intact between the secondary epidermal laminae and secondary dermal laminae, and the ultrastructural analysis of the cells showed their structural integrity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Horse; Histology; Laminae; Pedal biopsy; Podiatry